Modern Development in Conflict with Ecology: Kamla Markandaya’s The Coffer Dams - Vanza Ketan Punjabhai (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2022)
The bond between nature and man is visible in the literature throughout history, regardless of their culture, language, nation, or time period. The depiction of nature and its relationship to humans in the literature not only illustrates the mental, social, and cultural status of the characters, but also reveals the author's attitude toward the environment. In this paper, an effort is made to examine The Coffer Dams by Kamla Markandaya from an ecocritical standpoint. The researcher has examined how the chosen novel represents the influence of industrialization on environment and humanity. This paper also focuses on the extent to which eco-criticism theorizes not only the connections between literature and the environment, but also the relationship between the characters in the texts and their environments, as well as the nature of language, textuality, and the perception of space, boundaries, class, and power.